Arte na TV: reflexões sobre matérias de arte em telejornais paraenses - ANDRADE, Ana Paula Dias (Universidade Federal do Pará, 2017)
Art and communication, two areas of knowledge that can contribute with reflections and questions about human reality, and still need to be more approximated. This work proposes a partnership between the two fields, to the development of the critical and culturally enriched. The focal point chosen for the study is the mediation of the art by the television news from the state of Pará, in Brazil. Does the TV news value, encourage and give visibility to the guidelines on art, primarily the local art? In attempting to answer this and other questions, we plunged into a theoretical literature addressing issues related to language of the arts and of the television, the critic of the art and cultural journalism, raising pillars for the understanding of how the TV, as mass media, must act to make a correct the mediation of artistic information. From theoretical approach, it is observed in practice, news reports broadcasted on the TV news stations in open channels from Pará: Liberal TV (Globo) TV RBA (BAND) and TV Cultura do Pará (public broadcaster), chosen for this content analysis. In the survey, the subjects bring artistic themes, part of the contemporary scene. Collect material on distinct channels contributes to the observation of how the information of art is addressed in each one, if visibility is given to the issue, valuing it, and if there is incentive, motivation or collaboration with the formation of a public of art.